Analysis of functional capacity in post-covid patients (Research, Society and Development, 2022)
Covid-19 is caused by the Sars-CoV-2 virus, which presents itself in a systemic, cognitive or physical way. Patients affected by covid may have multisystemic conditions as sequelae, leading to reduced functional capacity and altered pulmonary and cardiac function. Objective: To verify the use of the 6 minute walk test (6MWT) and the short form – 36 (SF-36) as instruments to assess the functional capacity and quality of life of patients infected with covid. Methods: Were included cross-sectional studies, systematic, observational and cross-sectional reviews, clinical trials and data analysis were included in this research, as well as articles containing adult patients infected with covid-19, who entered physical therapy rehabilitation and the 6MWT and SF-36 were evaluated. Thus, being included, covid - 19, Sars-Cov 2, functional capacity tests, 6MWT, coronavirus infection, quality of life and SF-36. The following exclusion criteria were adopted: studies with incomplete data and studies without data from the control group, pediatric rehabilitation. Results: Initially, 43 articles were detected, of which 20 were used for better analysis, of these 14 were considered relevant, but 6 were excluded because they did not present outcomes of interest, due to incomplete data or lack thereof, leaving 8 articles, with a total of 616 volunteers and some systematic review articles. Conclusion: Therefore, it is concluded that the SF 36 detected mainly emotional and physical changes, due to the pathologies already installed in post-covid patients. The 6MWT assists in the assessment and control of functional capacity, assessing physical sequelae and contributing to the prescription of appropriate treatment.